Quantifying wage effects of offshoring: import- versus export-based measures of production fragmentation - Wolszczak-Derlacz, Joanna; Parteka, Aleksandra (Economics and Business Review, 2016)
In this paper we examine the implications of international fragmentation ofproduction on wages in the light of recent methodological developments in offshoringmeasurement. In particular, we compare the results stemming from two ways of quantifyingoffshoring – the traditional one based on import statistics and the one obtainedfrom the decomposition of gross exports and input-output information.In the empirical part of our study, we estimate the extended version of wage equation,rooted in the Ricardian model of skills, tasks and technologies where skill specificwages are explained by industry-specific measures of capital, skill supply and offshoringindices. The analysis is performed for a large panel (40 countries, 1995–2011and 13 manufacturing industries). The results of the FE setting indicate that regardlessthe way offshoring is measured it is negatively associated with wages. However,when the endogeneity is accounted for, this negative association is sustained only forthe export-based measures.